483 LIGAMENT ENGINEERING: THE RESPONSE OF BONE MARROW STROMAL CELLS TO HIGH-FREQUENCY STIMULATION AND UNIAXIAL STRETCH. Issue 1 (1st January 2007) - Esmende, S.; Petrigliano, F.; Barba, D.; Wu, B.; McAllister, D.
Abstract : Rupture of the anterior cruciate ligament (ACL) is one of the most common ligament injuries of the knee. Current ACL surgical strategies consist of using a local autograft or allograft to replace the native ligament. Decreased range of motion and weakness has been commonly associated with autografts. Allografts are associated with immunogenic rejection and a lack of available donors. Previous studies have shown that human bone marrow stromal cells (BMSCs) can be stimulated toward a fibroblast-like lineage. Although the exact mechanism underlying differentiation in response to mechanical stimulation remains unclear, these cells hold a great potential for use in ACL engineering. The aim of this project was to determine the effects of mechanically stimulating BMSCs under controlled frequency during in vitro cultivation. Specifically, we wanted to determine the potential synergistic effects of high-frequency mechanical stimulation to "prime" BMSCs prior to low-frequency uniaxial stretch. A high-frequency 60 Hz stimulation system was developed and characterized. Microporous scaffolds were constructed from biodegradable polycaprolactone polymer. BMSCs were harvested from Lewis rats, expanded in culture, and seeded at 1 × 10 6 cells per scaffold. The seeded cells were then exposed to a 10-minute regiment of sine-shaped vibration (60 Hz) with a peak-to-peak acceleration of 1.8 ± 0.1 m/sec 2 and a displacement amplitude of 67 ± 5 μm during a period of 7 days. The cells were then placed in a bioreactor cultivated for 7 days during which low-frequency (0.125 Hz) uniaxial strain (6%) was applied. Initial qRT-PCR data revealed that at 1 × 10 6 cell density, no up-regulation in gene expression was observed in stress-resistant biomarkers collagen I, collagen III, and tenascin C. Cell-seeding density was independently confirmed by cryosections stained with hematoxylin and eosin. Using higher cell density in this model system, future experiments will investigate the role of high-frequency stimulation independently and synergistically with other means of biomechanical stimulation.